ESTIMASI CADANGAN KLAIM IBNR: PENDEKATAN METODE BORNHUETTER FERGUSON DAN METODE MUNICH CHAIN LADDER - Azizah Azizah; Ardia Fatma Sari; Meidy Indhira Putri (MUST: Journal of Mathematics Education, Science and Technology, 2025)
Estimating claim reserves in an insurance company is crucial. Inaccuracy of the estimation results can affect the condition of an insurance company. Thus, the estimation results are expected to be close to the actual claims of a company. The purpose of this study is to compare the estimation of claim reserves using the Bornhuetter Ferguson and Munich Chain Ladder methods. The Bornhuetter Ferguson method utilizes internal information in the form of claim data and external information in the form of earned premium (company income derived from premiums paid by the insured). The Munich Chain Ladder method is a development of the Chain Ladder method that considers the correlation element between incurred claim data and paid claim data. In this study, both methods are applied to calculate the claim reserves of an insurance company in Malaysia. The estimation results obtained are the Bornhuetter-Ferguson method produces an estimate of claim reserves of RM2668458000 in paid data and RM3026005600 in incurred data, while the Munich Chain Ladder method produces an estimate of claim reserves of RM2938886000 in paid data and RM2134746600 in incurred data.